DETERMINING THE EFFICACY OF ISOXYL, A MYCOLIC ACID INHIBITOR, IN VITRO AGAINST MYCOBACTERIA OTHER THAN MYCOBACTERIUM TUBERCULOSIS (MOTT) STRAINS - Vaidya, Shashikant; Chitalia, Vidushi; Muley, Shreyasi; Koppikar, Geeta; Kulkarni, Mohan; Chowdhary, Abhay (LIFE: International Journal of Health and Life-Sciences, 2015)
Mycobacteria other than Mycobacterium tuberculosis (MOTT) cause infections more commonly in the presence of predisposing factors and underlying diseases.They are also notably resistant to commonly used antituberculosis drugs. Total 11 clinical isolates MOTT were included in the study.Drug susceptibility testing of these isolates was performed by Resistant Ratio method. Minimum inhibitory concentration (MIC) pattern of these isolates of MOTT to mycelia acid synthesis inhibitors namely, Isoxyl(ISO) and Isoniazid (INH) were determined by agar dilution and broth dilution method. Minimum bactericidal concentration (MBC) pattern of these isolates to ISO and INH werealso determined. Out of 11 MOTT isolates, 3 isolates were characterized as Mycobacteriumscrofulaceum, 3 isolates as Mycobacteriumfortuitum, 2 isolates as Mycobacteriumflavescens, 1 isolates as Mycobacterium terrae and 2 isolates as Mycobacteriumkansasi depending upon the results of biochemical tests.The MBC range of INH was found to be 0.025 to 6.4 μg/ml and of ISO was found to be 0.6 to 20 μg/ml. Bactericidal activity of ISO was 7.25 times lower than the activity of INH. It is well known that most MOTT species are more resistant to chemotherapeutic agents other than tubercle bacilli.The inhibitory activity of ISO was more to MOTT strains than Mycobacterium tuberculosis strains.There was low bactericidal activity of ISO to MOTT strains, but better than for Mycobacterium tuberculosis strains.